Sustainability of the Current Account: Evidence from Pakistan - Ahmad, Shabbir (International Journal of Economics and Financial Issues, 2017)
This study examines the sustainability of the current account deficit using Pakistani data over the period 1974-2013. Employing the intertemporal budget constraint model and using ARDL bound testing approach, it is concluded that there is a long run relationship between real exports and imports. However, the hypothesis of one to one relationship between the two variables does not hold in its strong form. This highlights the need for better policies to improve the current account balance in the long run. Keywords: Intertemporal Budget Constraint, Current Account Deficit, Cointegration, ARDL, Bound Testing JEL Classifications: F30, F32